Propuesta del modelo para mejorar la calidad de servicio al usuario en el MAGAP de Portoviejo - Vera Rivera, María Gabriela (2013)
The present work of investigation had as purpose propose a management model for improve the quality of service the user in the Ministry of Agriculture Livestock Acoacultura and Fisheries, for development of the proposal was conducted by compiling of information for analysis of the current situation of the institution, by brainstorming was identified the main criteria for study from areas of the MAGAP, for diagnosing service quality a survey was carried taking as sample at 100 people per the area of Agriculture, Livestock and Aviculture, with this instrument could be determined the degree of user satisfaction through the indicators of services, attention in offices, duration of service, bathrooms, schedules, doubts and suggestions, expectations of the service, having as result that an average of rating of 2, 8 that according to the scale is located between the parameters of unsatisfied, such reason was effected a diagram of cause and effect in which was exposed the main problem, then proposed a improvement alternative through a plan of action based on the norm ISO 9001.